Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (Conference Papers – American Sociological Association, 2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Sociology
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Dispossession, Class Formation, and the Political Imaginary of Colombia's Coffee Producers Over the Longue Durée: Beyond the Polanyian Analytic - Hough, Phillip A.; Bair, Jennifer (Journal of World-Systems Research, 2012)
For more than a decade, social scientists have been analyzing the implications of the neoliberal turn in development policy and the implications of market-led agrarian reform for agricultural producers in the global South. Among this work is a spate of recent scholarship celebrating a number of flagship movements, such as the Zapatistas in Mexico or the landless movement in Brazil, which are interpreted as efforts by rural communities to resist the threat posed by the commodification of livelihoods and the privatization of natural resources. In this article, we aim to problematize what we diagnose as the "Polanyian analytic" underlying accounts of the current conjuncture which emphasize the imminent potential of neoliberalism to spawn protective counter-movements of the sort described in The Great Transformation. We do so through an analysis of the Unidad Cafetero Nacional (UCN) movement, an organization of Colombian coffee farmers that effectively mobilized large numbers of cafeteros in the 1990s to protest the liberalization of the global coffee market and the decline of state support for the domestic coffee sector. While the UCN may be read as a struggle to resist the dispossession of Colombian coffee farmers, we argue that it represented a particular segment of rural producers who wanted, first and foremost, a restoration of their relatively privileged status within the political economy of Colombian agriculture. Our interpretation of the UCN suggests that whether movements emerge in response to neoliberalism depends on the political imaginaries of the social actors who would create them, and further, that these imaginaries are produced through processes of class formation over the longue durée that shape the meaning of dispossession in particular contexts.
Sociology
Keywords: Colombia; agriculture; coffee growers; coffee plantations; commodification; liberalization (finance); neoliberalism; privatization